Practices and Challenges in Implementing Inclusive Education in Philippine Elementary Schools - Beltran, Kennedy A.; Agripa, Shayna A.; Bustarga, Angela Janelle O.; Cruz, Katrina B. Dela; Marmol, Sharmine L.; Morallo, Sofia Jane A. (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Inclusive education has become a cornerstone of educational reforms globally. This study investigates practices and challenges to implementing inclusive education in elementary schools within the Pili East District during the 2024–2025 school year. Using an exploratory sequential mixed-methods design, the research combined qualitative interviews with a quantitative survey conducted among teachers teaching learners with special needs in mainstream classrooms. Findings show that schools strive to foster inclusivity but face barriers such as inadequate resources, limited parental involvement, and insufficient teacher training. Effective strategies include differentiated instruction, collaborative policies, and fostering supportive environments. A notable gap is the lack of collaboration between teachers and parents in identifying and addressing learners’ needs. The study recommends that the Department of Education require schools to document learners with special needs to improve data accuracy and better allocate resources. It also advocates for educational campaigns to strengthen the roles of stakeholders in promoting inclusive education.